2021
DOI: 10.3390/ani11082361
|View full text |Cite
|
Sign up to set email alerts
|

Role of Two-Dimensional Speckle-Tracking Echocardiography in Early Detection of Left Ventricular Dysfunction in Dogs

Abstract: Two-dimensional speckle-tracking echocardiography (2D–STE) is an advanced echocardiographic technique based on deformation imaging that allows comprehensive evaluation of the myocardial function. Clinical application of 2D–STE holds great potential for its ability to provide valuable information on both global and regional myocardial function and to quantify cardiac rotation and synchronicity, which are not readily possible with the conventional echocardiography. It has gained growing importance over the past … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 74 publications
(207 reference statements)
1
20
0
1
Order By: Relevance
“…In addition, myocardial deformation is important because it evaluate the myocardial contraction from base to apex (longitudinal strain), systolic shortening in the short-axis view (circumferential strain), and myocardial thickening from the endocardium to epicardium (radial strain). This allows interpretation of regional and global abnormalities with high predictive ability [ 16 , 32 ]. As the dogs included in this study are healthy and have the normal reference values of these parameters before surgery, the increased radial strain and FS% may be due to the induced cardiac wound, which stimulates the heart to work more to survive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, myocardial deformation is important because it evaluate the myocardial contraction from base to apex (longitudinal strain), systolic shortening in the short-axis view (circumferential strain), and myocardial thickening from the endocardium to epicardium (radial strain). This allows interpretation of regional and global abnormalities with high predictive ability [ 16 , 32 ]. As the dogs included in this study are healthy and have the normal reference values of these parameters before surgery, the increased radial strain and FS% may be due to the induced cardiac wound, which stimulates the heart to work more to survive.…”
Section: Discussionmentioning
confidence: 99%
“…Recent echocardiographic approaches such as two-dimensional speckle tracking echocardiography (2D-STE) and intraventricular pressure gradients (IVPG) calculated from color M-mode echocardiography create a breakthrough in cardiology research for the early diagnosis of cardiac dysfunctions, as compared with other traditional methods [ 16 , 17 , 18 ]. In the present report, the echocardiographic changes were evaluated using conventional echocardiography, 2D-STE and CMME, before and weekly after the implantation of the TEER in two clinically normal dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Speckle-track echocardiography (STE) is a novel non-invasive ultrasound imaging technology that enables the determination of global and regional function of myocardium independent of insonation angle and heart translational movements [8]. However, the STE approach was originally developed for the unique purpose of assessing LV function, numerous subsequent studies have shown that it can also be used to assess other cardiac chambers, like the LA [9]. The atrial longitudinal strain, which is derived through the application of STE to analyze myocardial deformation in atrial chambers, is the primary variable relevant for functional investigation of the LA, and it has a high level of reproducibility and feasibility [10].…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional speckle tracking echocardiography (2D-STE) is an advanced echocardiographic technique that allows comprehensive analysis of myocardial function by quantifying myocardial deformation. There is growing evidence that the parameters of this deformation analysis are superior to the conventional parameters for the early diagnosis of myocardial dysfunction ( 1 ). Suzuki et al evaluated the relationship between congestive heart failure (CHF) and myocardial function in cats with cardiomyopathies using 2D-STE.…”
mentioning
confidence: 99%